A study of Ngugi wa Thiong'o's later novels to assess his adaptation of dramatic techniques and Gikuyu oral traditions to the requirements of fiction - Erapu, Laban Omella (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1992)
This thesis examines Ngugi wa Thiong'o's later writings in order to establish the nature of his quest for a people's literature. It illustrates how the author attempts to break the barriers between traditional oral forms and the relatively new written forms in addressing a basically "illiterate" audience. The research begins with an exploration of Gikuyu oral literature as an essential background to Ngugi's later dramatic and fictional writings as distinct from his earlier literary works in which he initiates the dominant quest for a more just society. Ngugi's return to these roots constitutes the central "homecoming" that characterizes his search for new forms. The analysis is conducted through three significant chronological stages representing Ngugi's writings over a period of about a decade from the mid-1970s to the early 1980s. Each stage starts with a play and performance followed by a parallel novel, the first pair written in English and the subsequent ones in Gikuyu. The three stages - designated Transition, Homecoming and Realization - mark Ngugi's involvement in the promotion of Gikuyu culture and orature, both as a source of inspiration and as a cause to which he fully dedicates himself. The transitional stage depicts the convergence between conventional and traditional oral literary forms with which Ngugi begins to experiment. The second stage introduces significant departures as Ngugi begins to use the Gikuyu language as his primary medium of creative expression. The final stage demonstrates his ultimate assertion of the primacy of orality over the written word as a dynamic agent of transmission. The thesis concludes that Ngugi wa Thiong'o in these later works - while leaving the possibilities of his vision of a "New Earth" unfulfilled pioneers the African writers' climb down from an "ivory tower" to deal with the realities of the experience of the predominantly non-reading African masses, acknowledged as both recipients of and active participants in the relatively new written literature which purports to speak for their experiences and their times.
Keywords: NgÅ©gÄ© wa ThiongÊ¼o, 1938-; Oral tradition -- Kenya; Folk literature, Kikuyu